MAKSIMALISASI POTENSI PEMASARAN DIGITAL UMKM MANYARAN: STRATEGI COPYWRITING DAN HOOK YANG TERBUKTI EFEKTIF - Saefurrohman, Saefurrohman; Khristianto, Teguh; Hartono, Budi; Lusiana, Veronica (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
The entrepreneurs in Kelurahan Manyaran demonstrate substantial potential for UMKM development but face challenges in producing engaging and consistent digital content to sustain audience interest. The primary issue lies in limited understanding of copywriting techniques and the effective use of hooks. To address this, the FTII UNISBANK team, in collaboration with LPMK Manyaran, launched a community service program involving basic training in copywriting and hooks, AI-supported content creation, and ongoing mentorship. The program showed significant improvements in audience engagement and UMKM sales conversion, with an average engagement increase of 30%–50% within three months and a sales conversion rise from 5% to approximately 6.5%–7.5%. This sustained support aims to create a lasting positive impact, promoting business independence and fostering UMKM growth in the digital era.